PERBANDINGAN LATIHAN VISUALISASI DRILL DAN LATIHAN INTERAKTIF DRILL TERHADAP KETEPATAN SMASH BULU TANGKIS PADA PB SONE LAMPUNG SELATAN - Ulpa, Raffi; Siswoyo, Joan; Suwarli; Surisman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to compare the effects of visualization drill training and interaktif drill training on badminton smash accuracy among athletes of PB SONE South Lampung. The research used an experimental method with a two-group pretest posttest design. The sample consisted of 30 athletes divided into two groups, with 15 athletes in each group. The research instrument was a badminton smash accuracy test. Data analysis included normality and homogeneity tests, followed by hypothesis testing using paired sample t-tests and an independent sample t-test at a significance level of 0.05. The results showed that visualization drill training did not have a significant effect on smash accuracy, with a t-value of 0.584 < t-table of 2.145 and a significance value of 0.569 > 0.05. In contrast, interaktif drill training had a significant effect on improving smash accuracy, with a t-value of 5.432 > ttable of 2.145 and a significance value of 0.000 < 0.05. Furthermore, the results of the independent sample t-test indicated a significant difference between the two training methods, with a t-value of 3.633 > t-table of 2.048 and a significance value of 0.001 < 0.05. The training program was conducted for 8 weeks with a frequency of three sessions per week. In conclusion, interaktif drill training is more effective than visualization drill training in improving badminton smash accuracy among athletes of PB SONE South Lampung.